Progressive Gelfand-Shilov Spaces and Wavelet Transforms - Dušan Rakić; Nenad Teofanov (Journal of Function Spaces and Applications)
We discuss progressive Gelfand-Shilov spaces consisting of analytic signals with almost exponential decay in time and frequency variables. It is shown that such signals enjoy an additional localization property. We define wavelet transform and inverse wavelet transform in (progressive) Gelfand-Shilov spaces and study their continuity properties. It is shown that with a slightly faster decay in domain we may control the decay of the wavelet transform independently in each variable.